The diversity of burden for significant others of person with aphasia - Pinki; Pauranik, Apoorva (Journal of All India Institute of Speech and Hearing, 2013)
When a person suffers from a stroke and aphasia, life not only changes for him or her, but also for significant others (SO). Standardized and valid measures are available to identify severity and diversity of burden reported by SO of person with aphasia (PWA). The present aimed to investigate the extent of post stroke changes in experiences of SO of PWA in terms of daily situation and during conversation with PWA of different age groups. To describe changes in SO experiences in terms of educational status, family type, aphasia type and severity of PWA. Twenty five participants were rated on questionnaire related to extent of changes, interactional competence (IC), language and communication related activities (LCA), communication effectiveness (CE) and their own perspectives about PWA. 56% PWA were of 40-60 years of age, 40% were graduates, 56% had anterior aphasia, 48% had moderate severity and 52% were staying in nuclear families. Paired t-test indicated significant mean difference between pre and post stroke experiences of SO at 0.001 level. Majority of the SO perceived their conversations with the PWA as being less stimulating and enjoyable than conversation before stroke onset. The communicative responsibilities of the SO were perceived to have increased consequentially; interaction competence and communication effectiveness of population has decreased significantly. Chi square result suggests highly significant (p< .001) association of education, type, severity and IC, CE and LCA of PWA. On the other hand, relation between competencies of PWA and type of family had border-line association(P <0.0460). Denial or unawareness about the perceptions of burden was found particularly in nuclear families. Post stroke aphasia leads to emergence of negative psychosocial consequences and apportionment of communicative burdens to SO. Future direction: To design and conduct family oriented intervention that includes communication partner training and to investigate its outcome combination of impairment based language intervention.